1997
DOI: 10.1055/s-2007-972616
|View full text |Cite
|
Sign up to set email alerts
|

After-Effects of a High Altitude Expedition on Blood

Abstract: The aim of the study was to investigate blood alterations caused by altitude acclimatization which last more than few days after return and might play a role for exercise performance at sea level. Measurements were performed in 12 mountaineers before, during and either 7/8 or 11/12 days after a Himalaya expedition (26-29 days at 4900 to 7600 m altitude). [Erythropoietin] rose only temporarily at altitude (max. +11 +/- 1 [SE] mu/ml serum). After return hemoglobin mass (initially 881 +/- 44 g, CO-Hb method) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 6 publications
4
29
2
Order By: Relevance
“…Nevertheless, decreased plasma osmolality and plasma total proteins observed in our study after the sojourn (P<0.05) suggest, indirectly, an increased plasma volume after the sojourn and consequently a lesser haemoconcentration. Identical conclusions were reached by Bo¨ning et al (1997), who showed that calculated plasma volume was increased at sea level after a high altitude stay. From our results, it seems that renal function is not involved, since osmolar and freewater clearances appeared unchanged after the sojourn.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, decreased plasma osmolality and plasma total proteins observed in our study after the sojourn (P<0.05) suggest, indirectly, an increased plasma volume after the sojourn and consequently a lesser haemoconcentration. Identical conclusions were reached by Bo¨ning et al (1997), who showed that calculated plasma volume was increased at sea level after a high altitude stay. From our results, it seems that renal function is not involved, since osmolar and freewater clearances appeared unchanged after the sojourn.…”
Section: Discussionmentioning
confidence: 71%
“…Changes in plasma volume and/or red cell mass have to be considered when [Hb] or PCV increases at altitude. During a 3-month stay at an altitude above 5000 m, Bo¨ning et al (1997) documented an increase of total body haemoglobin of 123 g, equivalent to a volume of 360 ml of erythrocytes. At moderate altitude (2300 m), an increase of the total body haemoglobin of 107 g was measured in swimmers of the German national team after a sojourn of 3 weeks (Schmidt et al 1994).…”
mentioning
confidence: 99%
“…Erythropoietin -A few hours after exposure to hypobaric hypoxia, the secretion of renal erythropoietin increases [34][35][36][37] . As it stimulates the synthesis of red blood cells, in approximately one week it significantly increases the concentration of hemoglobin and, therefore, the capacity of transporting O 2 in the blood 38 .…”
Section: Endothelial and Blood Alterations -Endothelinmentioning
confidence: 99%
“…The physiological mechanisms are the following: 1) increase in the pulmonary ventilation 39 ; 2) reduction in the HR previously increased in the acute response 22,39 ; 3) decrease in the plasmatic volume 39,40 ; 4) reduction of the accumulation of lactate in the blood during submaximal exercise in relation to the more elevated levels of acute response 39 ; 5) improvement of the cardiorespiratory capacity for exercise, also related to the initial exposure to the hypobaric hypoxia 23,41 ; 6) increase in the secretion of renal erythropoietin, in the hemoglobin mass and in the hematocrit 34,36,37,42 .…”
Section: Acclimatizationmentioning
confidence: 99%